Study on fatigue experiment for transverse butt weldsunder 2G and 3G weld positions - Sung-Wook Kang; Yong-Man Park; Beom-Seon Jang; Yu-Chul Jeon; Seong-Min Kim (International Journal of Naval Architecture and Ocean Engineering, 2015)
Although the transverse butt weld method with ceramic backing strip has been widely used in various industrial fields for its fabricational convenience, it is rarely used in offshore industries since the fatigue strength of the weld joint has not been proved sufficiently. This study conducted fatigue tests for series of butt weld specimens with horizontal (2G) and vertical (3G) welding positions in order to verify the fatigue strength compared to S-N curve by DNV (Det Norske Veritas), IIW (International Institute of Welding) and Eurocode 3. The difference of the 2G specimens and the 3G specimens are investigated in terms of angular distortion and the effect on the fatigue strength are analyzed.